Using Text Clusters to Support Student Imagining, Wondering, Questioning, and Discovering - William P. Bintz (Current Issues in Middle Level Education, 2025)
This article describes an unexpected playground experience that occurred between the author, a reading educator and former middle grades teacher, and his six-year-old granddaughter. The experience became the inspiration and impetus to provide an introduction to, and a rationale for, the concept of text clusters to middle grades teachers. The concept of developing and implementing text clusters in the classroom is driven by inquiry and based on one question: How can middle school teachers develop and implement text clusters to help their students actively engage in imagining, wondering, questioning, and discovering? It shares and illustrates examples of text clusters. It also shares samples of instructional strategies teachers can use with text clusters to actively engage students in imagining, wondering, questioning, and discovering. It ends with some concluding thoughts inspired by the picturebook What We’ll Build: Plans for Our Future Together (Jeffers, 2020).